The effect of red grape juice and exercise, and their combination on parkinson's disease in rats - Fatemeh Eshraghi-Jazi; Hojjatallah Alaei; Hamid Azizi-Malekabadi; Mahin Gharavi-Naini; Aliasghar Pilehvarian; Zahra ciahmard (Mashhad University of Medical Sciences, 2012)
Objective: Parkinson's disease (PD) is one of the most common neurodegenerative disorders which is characterized by tremor, rigidity, bradykinesia and postural disturbances. Studies indicate that grape juice and exercise may have beneficial effects on neurodegenerative disorders. Therefore, in the present study, we evaluated the effects of red grape juice (GJ) together with treadmill running on animal model of PD. Materials and Methods: 30 male Wistar rats were divided randomly into Sham, PD, PD treated with GJ (PD-GJ), PD treated with exercise (PD-Ex), and PD treated with GJ associated with exercise (PD-GJ-Ex) groups with six rats in each. In order to obtain the PD model, 6-OHDA was infused into left substantia nigra pars compacta. In order to prove that the lesions are created and to estimate their extent, apomorphine was administered (i.p.) and total number of induced rotations was recorded during 60 minutes. Exercise was applied by treadmill and GJ was added into drinking water for 30 days and rotations test was performed again. Results: Our results indicate that there was a significant difference in number of rotations between PD and Sham groups (p